Consumer Preferences and Perceptions of Ayurveda Toothpaste: A Shift towards Natural Oral Care - Sharma , Rajeev; Patel , Malay; Pareek, Prashant; Dubey , Punit (Journal of Drug Delivery and Therapeutics, 2025)
Growing demand for natural and holistic personal care products results from consumers of today being more knowledgeable and proactive about their health. In the sphere of oral care, this change has resulted in a new classification— Ayurvedic toothpaste. Ayurvedic toothpaste is made using Ayurvedic principles, an ancient Indian school of medicine stressing natural components to promote whole well-being. Ayurvedic toothpaste is made of plant extracts, essential oils, and naturally occurring minerals recognized for their healing qualities unlike regular toothpaste, which often includes synthetic chemicals and artificial additives. Many customers of contemporary oral care choose Ayurvedic toothpaste as they believe chemical-based toothpaste to be possibly dangerous. While providing good defense against typical dental problems like cavities, plaque buildup, bad breath, and gum disorders, herbal formulations are said to be milder on the teeth and gums. Ayurvedic toothpaste is also popular for those looking for a natural and sustainable method of oral care as it combines elements with antibacterial, anti-inflammatory, and strengthening qualities. Ayurvedic toothpaste is becoming more and more popular as knowledge of the advantages of herbal substitutes keeps growing and as a safer and better way to preserve oral health. The increasing inclination for such goods reflects a larger trend toward natural and organic personal care solutions, therefore supporting the relevance of old knowledge in contemporary medicine. The purpose of the paper is to highlight the core advantage of herbal tooth paste comparing with conventional toothpaste. This paper examine various factors which affect customer buying decision in the category of toothpaste category.Keywords: Herbal, Ayurvedic, Dental care, Customer preferences.